2017
DOI: 10.3390/ijms18081651
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasminogen Activator Inhibitor Type 1 in Pathologies of Female Reproductive Diseases

Abstract: Normal pregnancy is a state of hypercoagulability with diminishing fibrinolytic activity, which is mainly caused by an increase of plasminogen activator inhibitor type 1 (PAI-1). PAI-1 is the main inhibitor of plasminogen activators, including tissue-type plasminogen activator (tPA) and urokinase-type plasminogen activator (uPA). In human placentas, PAI-1 is expressed in extravillous interstitial trophoblasts and vascular trophoblasts. During implantation and placentation, PAI-1 is responsible for inhibiting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 137 publications
2
37
0
1
Order By: Relevance
“…Thus, significantly increased levels of PAI-1 produced by senescent ESCs, may not only be responsible for triggering paracrine senescence in the neighboring cells, but also, may play role in the prevention of trophoblast invasion mediating various reproductive diseases. Indeed, it was shown that elevated levels of PAI-1 accompany such pathologies as recurrent pregnancy loss, repeated implantation failures and unexplained female infertility [42, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, significantly increased levels of PAI-1 produced by senescent ESCs, may not only be responsible for triggering paracrine senescence in the neighboring cells, but also, may play role in the prevention of trophoblast invasion mediating various reproductive diseases. Indeed, it was shown that elevated levels of PAI-1 accompany such pathologies as recurrent pregnancy loss, repeated implantation failures and unexplained female infertility [42, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…One example of this may be through NFκB activation of PAI-1. Multiple reports state that PAI-1 expression is significantly increased in the placenta of women with PE [74,75] and studies have shown PAI-1 can be induced via TNFα activation of NFκB, to decrease EVT invasion [63,64].…”
Section: Evt Function and Nfκb Actions In Preeclampsiamentioning
confidence: 99%
“…Serpin Family E Member 1 ( SERPINE1 ), which is the inhibitor of tissue plasminogen activator and urokinase [107] that regulates fibrinolysis [108], appeared to be in the fifth place of the table. The SERPINE1 gene mediates the anti-apoptotic effect in the endothelial cell [109].…”
Section: Resultsmentioning
confidence: 99%